2014
DOI: 10.1039/c4tc00652f
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-based biopolysaccharide proton conductors for synaptic transistors on paper substrates

Abstract: The chitosan-based paper synaptic transistors were successfully used as artificial synapses for emulating biological synaptic functions, including excitatory postsynaptic current, paired-pulse facilitation, dynamic filtering and spatiotemporally correlated signal processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 40 publications
1
85
0
2
Order By: Relevance
“…It is noteworthy that in most cases of electrolyte -gated synaptic transistors, facilitation of I Post is observed. [ 17,22,38,39 ] Facilitative functions can be equally reproduced in OECTs, by applying negative presynaptic gate pulses and thereby increasing channel conductance by inducing electrochemical doping above the native level of the channel. [ 9 ] Facilitation is also expected to arise in accumulation mode OECTs, in which the transistor is in the OFF state at zero gate voltage.…”
Section: Communicationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that in most cases of electrolyte -gated synaptic transistors, facilitation of I Post is observed. [ 17,22,38,39 ] Facilitative functions can be equally reproduced in OECTs, by applying negative presynaptic gate pulses and thereby increasing channel conductance by inducing electrochemical doping above the native level of the channel. [ 9 ] Facilitation is also expected to arise in accumulation mode OECTs, in which the transistor is in the OFF state at zero gate voltage.…”
Section: Communicationmentioning
confidence: 99%
“…[17][18][19] Regarding organic devices, it is worth mentioning that various plasticity functions were also realized with devices based on PEDOT:PSS, [ 20 ] Nafi on, [ 21 ] and Chitosan. [ 22 ] Even more recently, OECTs interfaced with cellular systems were proposed as neuroinspired computational platforms, [ 23,24 ] expanding thus the functionality boundaries of the current neuromorphic devices. Given the properties of OECTs (e.g., ionic-to-electronic transduction, amplifi cation, lateral gating), a unique opportunity arises to explore these devices as candidates for neuromorphic devices with enhanced functionalities.…”
Section: Doi: 101002/adma201503674mentioning
confidence: 99%
See 1 more Smart Citation
“…This is an emerging material in the field of organic electronics with intriguing attributes. Wu et al showed the potential for the use of CS in organic electronics through the fabrication of synaptic transistors on paper substrates that show a high proton conductivity of 6 × 10 −3 S cm −1 at room temperature . In another interesting scientific study, solution‐processed graphene oxide/CS composite films were reported to behave as an excellent proton‐conducting electrolytes with a high specific capacitance of ≈3.2 µF cm −2 at 1.0 Hz …”
Section: Introductionmentioning
confidence: 99%
“…Currently, many synaptic functions, such as long-term memory, short-term memory, and excitatory postsynaptic current, are also mimicked by electric-double-layer (EDL) synaptic transistors gated by a proton conducting film 11. Broad spectrum proton conducting films, such as nanogranular SiO 2 films, KH550-GO solid electrolyte, and chitosan membrane, have been proposed as the gate medium of synaptic transistors 121314. Given the significance of gate dielectrics to transistor-based synaptic devices, mobile protons in such proton conductor electrolytes assume an important role in the application of these devices 1516.…”
mentioning
confidence: 99%